A turkey for Thanksgiving - Bunting, Eve, 1928-; De Groat, Diane (New York : Clarion, 1991)
Mr. and Mrs. Moose try to invite a turkey to their Thanksgiving feast.
Elem. School Library Collection
School Library Journal
Wilson's Children
4.5
K-3
K-3
Keywords: Moose -- Fiction; Thanksgiving Day -- Fiction; Turkeys -- Fiction; Moose -- Fiction; Thanksgiving Day -- Fiction; Turkeys -- Fiction